Low-intensity pulsed ultrasound regulates osteoblast-osteoclast crosstalk via EphrinB2/EphB4 signaling for orthodontic alveolar bone remodeling - Zhou, Jie; Zhu, Yanlin; Ai, Dongqing; Zhou, Mengjiao; Li, Han; Fu, Yiru; Song, Jinlin (Frontiers in Bioengineering and Biotechnology, 2023)
The limited regenerative potential of periodontal tissue remains a challenge in orthodontic treatment, especially with respect to alveolar bone remodeling. The dynamic balance between the bone formation of osteoblasts and the bone resorption of osteoclasts controls bone homeostasis in orthodontic. The osteogenic effect of Low-intensity pulsed ultrasound (LIPUS) is widely accepted, so LIPUS is expected to be a promising method for alveolar bone regeneration. Osteogenesis is regulated by the acoustic mechanical effect of LIPUS, while the cellular perception, transduction mode and response regulation mechanism of LIPUS stimuli are still unclear. In this study, the effects of LIPUS on orthodontic alveolar bone remodeling were proved by rat orthodontic tooth movement (OTM) models. LIPUS was found to promote differentiation and EphB4 expression in bone marrow mesenchymal stem cells (BMSCs)-derived osteoblasts in vitro, particularly when cells were directly co-cultured with bone marrow monocytes (BMMs)-derived osteoclasts. LIPUS activated the EphB4 receptor on the osteoblasts membrane, transduced LIPUS-related mechanical signals to the intracellular cytoskeleton, and gave rise to the nuclear translocation of YAP in the Hippo signaling pathway, thus regulating cell proliferation and osteogenic differentiation. This study shows that LIPUS modulates bone homeostasis by osteoblast-osteoclast crosstalk via EphrinB2/EphB4 signaling, which benefits the balance between OTM and alveolar bone remodeling.